Analisis Buku Ajar Bahasa Arab Tingkat Madrasah Ibtidaiyah Perspektif Amani dan Awatif - Moh. Buny Andaru Bahy; Mirwan Ahmad Taufiq (Taqdir, 2021)
The selection of quality textbooks is of particular concern in the world of education, because textbooks are considered as one of the most important aspects of learning. So, the books that have been circulated should have complied with the applicable textbook assessment criteria. Therefore, this study was written to determine the quality of Arabic language books for 5th grade students of Madrasah Ibtidaiyah published by the Ministry of Religion of the Republic of Indonesia on the basis of Amani and Awatif book standards. This study uses a qualitative descriptive approach based on literature (Library Research). The data in this study were obtained from the Arabic language textbooks for grade 5 students by using document classification techniques and then analyzing them. Based on the analysis that has been done, the researchers found the results that the 5th grade Arabic textbooks published by the Ministry of Religion of the Republic of Indonesia were of good quality. However, there are still some aspects of the book that need improvement and need to be improved. As in the completeness of writing the muqaddimah of the book and the need to maximize aspects of activities and development of Arabic learning media for 5th grade students of Madrasah Ibtidaiyah.